Alpha-solanine inhibits cell proliferation via mitochondrial dysfunction and inhibin synthesis in mouse testis In vitro and In vivo. (November 2019) - Park, Sunwoo; Park, Min Young; Song, Gwonhwa; Lim, Whasun
Abstract: Sertoli and Leydig cells provide key supporting roles in spermatogenesis. Various toxins have been studied in the TM3 and TM4 mouse testis cell lines to identify their regulatory effects. Alpha-solanine (α-solanine), a toxic compound found in the potato, has cytotoxic effects on various cells, including cancer cells. However, the effect of α-solanine on testis function has not been identified. In this study, we verified for the first time the anti-proliferative effect of α-solanine in mouse testes. α-Solanine reduced cell viability in TM3 and TM4 cells and reduced the expression of the cell cycle checkpoint genes Ccnd1 and Ccne1 . We also detected changes in the mitochondrial membrane potential (MMP) and in the cytosolic calcium and intracellular signal pathways in both cell lines. α-Solanine induced AKT, P70S6K, S6, ERK1/2, and JNK activation in mouse testis cells. In addition, the inhibition of AKT with a pharmacological inhibitor (LY294002) demonstrated more synergic anti-proliferative effects than in the TM3 and TM4 cell lines treated only with α-solanine. Inha and Inhba mRNA expression also decreased in both cell lines and α-solanine i.p. injected mouse testes. Collectively, the results from this study verify the toxic effects of α-solanine on testes and male reproductive function. Graphical abstract: A schematic illustration of the anti-proliferation activity of α-solanine in mouse Leydig and Sertoli cells. α-solanine disrupts the membrane potential of mitochondria and accumulates cytosolic calcium ions in both TM3 and TM4 cells. It increases the activation of AKT, P706SK, S6, ERK1/2, and JNK proteins in TM3 and TM4 cells. It also inhibits cell proliferation via the downregulation of Ccnd1, Ccne1, Inha, and Inhba mRNA expression. Collectively, α-solanine disrupts cell proliferation and function in mouse testes.Image 1 Highlights: Alpha-solanine induces apoptosis and cell cycle arrest of mouse testicular cells. Alpha-solanine increases mitochondrial dysfunction of testicular cells. Alpha-solanine disrupts the calcium homeostasis necessary for testicular cells. Alpha-solanine may lead to the failure of spermatogenesis in mice.